2021
DOI: 10.1016/j.ejim.2021.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste and obesity

Abstract: For more than 50 years, there has been evidence for greater consumption of sweet-foods in overweight humans and animals, relative to those that have a normal weight. Furthermore, it has long been suggested that energy deficit resulting from dieting, while moving the individual from a higher weight set point, would result in heightened susceptibility to palatable tastants, namely to sweet tastants. This was the motivation behind the first studies comparing sweet taste perception between individuals with obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…On the one hand, normal gustatory function is needed for normal intake of food and healthy nutrition, and gustatory dysfunction may lead to poor appetite and malnutrition (Fuchida et al, 2013). On the other hand, poor taste acuity may change eating behavior and lead to dietary overconsumption, which increases the risk for obesity (Ribeiro and Oliveira‐Maia, 2021). Additionally, among various overweight groups, only the obesity class II group exhibited reduced taste scores, suggesting the gustatory function was notably affected only when the overweight reached a certain degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, normal gustatory function is needed for normal intake of food and healthy nutrition, and gustatory dysfunction may lead to poor appetite and malnutrition (Fuchida et al, 2013). On the other hand, poor taste acuity may change eating behavior and lead to dietary overconsumption, which increases the risk for obesity (Ribeiro and Oliveira‐Maia, 2021). Additionally, among various overweight groups, only the obesity class II group exhibited reduced taste scores, suggesting the gustatory function was notably affected only when the overweight reached a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, underweight individuals were also associated with poor appetite and low taste sensitivity to bitter taste (Fuchida et al, 2013). However, previous evidence does not consistently support the notion that obese individuals have altered taste sensitivity, or associates tastespecific impairment with obesity (Ribeiro & Oliveira-Maia, 2021). This inconsistency may result from their limited sample sizes and heterogeneity of taste assessments.…”
Section: Introductionmentioning
confidence: 95%
“…The former have lower sensitivity to sweet and fatty tastes but like sweet and fat more than the latter" [160]. Furthermore, it is difficult to reach an objective evaluation of the hedonic value of any flavour, especially in disease states [161][162][163]. Hedonic values are generally studied indirectly on the basis of eating habits, choices in experimental situations, the study of intracerebral opiates and dopamine, evoked potentials, electrical activity and brain imaging [161].…”
Section: Alteration Of the Reward System High-fat Diet And Obesitymentioning
confidence: 99%
“…Based on the observation that the consumption of ultra-processed food is greater in individuals with overweight and obesity [29,30], it is widely assumed that the liking of sweet foods may contribute to the development of obesity. However, research on the relationship between sweet taste preferences and obesity revealed mixed results and remains inconclusive [31]. For example, Sobeck et al investigated 150 children and found twice as many obese children in a group that preferred high sweet taste as compared to a group that preferred low sweet tastes [32].…”
Section: Sweet Taste Preference and Obesitymentioning
confidence: 99%
“…In addition, it has been shown in mice that chronic low-grade inflammation, due to obesity, diminishes the number of taste buds in gustatory tissues [37]. However, systematic studies in humans addressing the association between sweet taste threshold and obesity (e.g., BMI) reveal inconclusive results [31]. While some studies found support for a negative relationship between BMI and sweet (and other) taste perceptions [38][39][40], other studies found no effects [41][42][43][44], or even reported rather enhanced than reduced sweet taste sensitivity [45,46].…”
Section: Sweet Taste Preference and Obesitymentioning
confidence: 99%